Surgical treatment and complications of operations in acute pancreatitis severe - I. A. Kaprin; Z. E. Eldarova; V. P. Glabai (Исследования и практика в медицине)
In this reviewing article there are discussed such topics as modern classification of acute pancreatitis, indications for surgical treatment of severe and, first of all, infected pancreatic necrosis, modern tendencies in this problem and controversial issues of it. The analysis of two different methods of surgeries («closed» and «open») for drainage of retroperitoneal space depending on the scale of necrotic lesion has been carried out. The perspective use of the natural transluminal endoscopic surgery (ENOTES) in the treatment of acute pancreatitis, complicated by abdominal compartment syndrome, is shown. The frequency of intraoperative and early complications after «closed» and «open» surgical interventions for severe acute pancreatitis has been reviewed; also recognition of the complications, the prevention of their occurrence and the choice of surgical or conservative methods of treating the complications.